(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, students’ nervous tension was determined using the Spielberger-Khanin test, and based on the results of the analysis, teaching staff can focus on an individual approach to students or on the use of unique advanced technologies in classroom processes, based on the characteristics of the group, and warn some students against their own actions, work on oneself, adapt to different environmental conditions, were analyzed through test results. The study was conducted with students of Fergana State University in 2022-2024, while during the period of intensive development, diseases of the nervous system become more frequent, exams become more stressful, family problems, and the work process. When explaining the cases of young organisms, it was concluded that the formation of a normal state of everyday life in them leads to the normalization of depressive states and extreme aggressiveness.